The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3855/jidc.9862
|View full text |Cite
|
Sign up to set email alerts
|

High resistance to tetracycline and ciprofloxacin in bacteria isolated from poultry farms in Ibadan, Nigeria

Abstract: Introduction: Resistance to ciprofloxacin and tetracycline is increasing in the food chain especially in E. coli strains and more worrisome will be occurrence of extended-spectrum beta-lactamase (ESBL) producers among ciprofloxacin-and tetracycline-resistant isolates. This study was undertaken to investigate the occurrence and mechanism of ciprofloxacin-, tetracycline-and ESBL-resistant bacteria in poultry in Ibadan, Nigeria. Methodology: Bacteria were isolated from poultry feces in two farms in Ibadan and ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…This study also revealed that isolates from chicken droppings showed high resistance properties toward ampicillin, augmentin, tetracycline, and trimethoprim- sulfamethoxazole followed by cefoxitin and chloramphenicol. The significant proportion of resistance against the above antibiotics was also reported from Bangladesh, 21 Nigeria, 18 , 30 Ethiopia, 20 Vietnam, 31 and China. 25 Moreover, the current study recorded higher resistance to ampicillin-sulbactam.…”
Section: Discussionmentioning
confidence: 86%
“…This study also revealed that isolates from chicken droppings showed high resistance properties toward ampicillin, augmentin, tetracycline, and trimethoprim- sulfamethoxazole followed by cefoxitin and chloramphenicol. The significant proportion of resistance against the above antibiotics was also reported from Bangladesh, 21 Nigeria, 18 , 30 Ethiopia, 20 Vietnam, 31 and China. 25 Moreover, the current study recorded higher resistance to ampicillin-sulbactam.…”
Section: Discussionmentioning
confidence: 86%
“…Previously, only a few reports from Nigeria provided draft genome sequence analyses, mainly concerning multidrug-resistant E. coli strains isolated from humans and chicken [52,53]. Whilst three ESBL E. coli poultry isolates belonged to ST6359 [52], the poultry E. coli isolates reported by Sharma et al, were assigned to ST131 and ST162 respectively. The human E. coli isolates were assigned to six different STs which included ST131, ST617, ST542, ST398, ST4143 and ST398 [53].…”
Section: Plos Onementioning
confidence: 99%
“…Tetracycline resistance of avian pathogens has been reported by several workers (Kolar et al, 2002;Omoya and Ajayi, 2016;Ayandiran et al, 2018). In a similar study conducted by Obeng et al, (2012), 32.6% (63/193) of the E.coli isolates from free range chicken in Australia were phenotypically tetracycline resistant.…”
Section: Genotypic Resistance Of Enterobacteriaceaementioning
confidence: 64%